2020
DOI: 10.22146/jmpf.48944
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Potentially Inappropriate Medications in Hospitalized Geriatric Patients in 2 Hospital in Jakarta using STOPP START Criteria

Abstract: Geriatric patients have more comorbidities and often receive polypharmacy prescriptions. The prevalence of inappropriate drug use in geriatric patients is in the range of 11.5% -62.5%. The consequence of polypharmacy is Adverse Drug Reactions (ADR). An effort to reduce the occurrence of medication errors in geriatric patients is the STOPP and START criteria. This study aimed to identify PIMs (Potentially Inappropriate Medications) and PPO (Potentially Prescribing Omission) in geriatric patients according to ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
(4 reference statements)
1
2
0
3
Order By: Relevance
“…23 A previous study in 2 hospitals in Jakarta, Indonesia, found that polypharmacy is an independent risk factor for PIMs incidence. 24 From those previous research, it may be declared there is a correlation between number of medications used and PIMs. [20][21][22][23][24] As seen in Table 1, cardiovascular and endocrine disorders rank second and third in samples, which can be seen as a factor leading to polypharmacy on this research.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…23 A previous study in 2 hospitals in Jakarta, Indonesia, found that polypharmacy is an independent risk factor for PIMs incidence. 24 From those previous research, it may be declared there is a correlation between number of medications used and PIMs. [20][21][22][23][24] As seen in Table 1, cardiovascular and endocrine disorders rank second and third in samples, which can be seen as a factor leading to polypharmacy on this research.…”
Section: Discussionmentioning
confidence: 97%
“…24 From those previous research, it may be declared there is a correlation between number of medications used and PIMs. [20][21][22][23][24] As seen in Table 1, cardiovascular and endocrine disorders rank second and third in samples, which can be seen as a factor leading to polypharmacy on this research. This result is similar to two previous studies, namely studies in Malaysia and Finland, which showed that the occurence of polypharmacy among geriatrics was related to the high prevalence of cardiovascular diseases and diabetes mellitus.…”
Section: Discussionmentioning
confidence: 97%
“…al. [6] yang menyatakan kejadian PIM sebedar 35,48% dan kejadian PPO sebesar 6,45% [6]. Angka kejadian PIM dan PPO dalam penelitian lebih tinggi dibandingkan hasil penelitian Rusdi, et al [14] yang mengungkapkan kejadi PIM sebesar 1,9% dan kejadian PPO sebesar 3,8%.…”
Section: Hasil Dan Pembahasanunclassified
“…Perubahan fisiologis menyebabkan perubahan farmakokinetik dan farmakodinamik obat pada pasien geriatri. Pasien geriatri cendrung memiliki banyak komorbiditas yang menyebabkan pemberian resep polifarmasi [6]. Polifarmasi adalah penggunaan bersamaan 5 atau lebih obat.…”
unclassified
See 1 more Smart Citation